Relationship Between Dietary Pattern And Blood Glucose Levels In Patients With Diabetes Mellitus In Wonoayu Village - Nafisa Dwi Kartika Hamzah; Tanty Wulan Dari; Dony Sulystiono; Siti Maimuna (Global Ten Public Health and Nursing Journal, 2025)
Diabetes mellitus (DM) is a chronic metabolic condition characterized by elevated blood glucose levels caused by problems with insulin secretion and function. Proper nutritional management is a key component in controlling blood glucose. Stable blood sugar levels can be maintained with a nutritious diet and avoiding unhealthy foods. This study used a cross-sectional methodology and a descriptive analytical strategy. Thirty-four people with diabetes mellitus in Wonoayu Village were sampled using a purposive sampling technique. Data were collected through a 24-hour food recall form and blood glucose measurements using a glucometer. Data were analyzed using the Chi-Square test. The study findings showed a strong correlation between dietary habits and blood glucose levels (p = 0.000). Compared with patients with poor dietary habits, individuals with good dietary habits tended to have normal blood glucose levels. This study demonstrates the importance of dietary habits in regulating blood glucose levels, including the type, amount, and timing of meals. To improve adherence to the recommended diet for people with diabetes mellitus, education about healthy eating is crucial.